MENGUCAPKAN SALAM KEPADA NON MUSLIM DALAM PERSPEKTIF FIQIH - Tauhid, Moh. (Al-Usroh : Jurnal Hukum Keluarga Islam, 2023)
Fiqh also has the function in determining the practical laws that might be followed by Muslims in various aspects of life, such as worship, Muamalah (transactions), and family. Fiqh also helps apply Islamic teachings in the context of modern times, even though the basic laws still apply, and allows adjustments in technical matters that did not exist at the time of the Prophet Muhammad SAW. It based on verses of the Qur'an and Hadith, which often have deep and complex meanings. The purpose of this study was describe, analyze, and provide an interpretation of the concept of greeting, saying greetings, and responding to greetings from non-Muslims from a Fiqh perspective. The method applied in this research is library research. The result is that the concept of greeting in Islam has a deep dimension of peace, tolerance, harmony, and affection between individuals and society. Although there are variations in interpretation and practice within the perspective of Fiqh, these principles teach Muslims to maintain an open, respectful, and compassionate attitude in interactions with all people, including non-Muslims. Then, in terms of answering greetings from non-Muslims, a Muslim can answer with different answers, namely by answering with wa'alaikum, 'alaika aw wa'alaika, and ma qulta. Thus, it hoped that this research could provide additional insight for religious people that reflected peace, tranquility, and safety in all aspects of life.